Efficacy and safety of acupuncture combined with auricular acupressure for smoking cessation: A study protocol of a multicentre, randomized, controlled clinical trial - Zeng, Jinchun; Liao, Yizu; Wei, Xiaojing; Chen, Guangxian; Cai, Zibin; Chen, Min; Gou, Yanhua; Lin, Guohua (Frontiers in Neurology, 2022)
Background Nicotine dependence is an addictive behavioral disease facilitated by habitually smoking cigarettes. In many countries, acupuncture and auricular acupressure have attracted growing attention as complementary or alternative treatments for smoking cessation; however, there is a lack of rigorous randomized, controlled studies evaluating the combination of these two interventions specifically for smoking cessation. The aim of this study is to evaluate the efficacy and safety of using acupuncture combined with auricular acupressure (A&AA) to increase the rates of smoking cessation and ultimately reduce the rates of relapse. Methods This is a multicentre, prospective, parallel, randomized, controlled trial. A total of 360 patients with severe nicotine dependence will be randomized into test (A&AA) or control (nicotine replacement therapy, NRT) groups. The test group will be treated with A&AA twice weekly, while the control group will use an NRT patch daily. All treatments will be administered for 8 weeks, with a follow-up period of 4 months. The primary outcome will be the smoking abstinence rate at week 24, with a combined safety assessment. The secondary outcomes will be smoking cessation rates at other timepoints, saliva cortisone test results, and scores on the Fagerstrom Test for Nicotine Dependence, the Autonomy over Tobacco Scale, the Hamilton Anxiety Rating Scale, the Self-rating Anxiety Scale, and the Pittsburgh Sleep Quality Index. The cost of treatment will also be used to evaluate the economic effects of different smoking cessation interventions. Statistical analysis on the data collected from both the intention-to-treat (all randomly assigned patients) and per-protocol (patients who complete the trial without any protocol deviations) patients, will be performed using the statistical software package, IBM SPSS 27.0. Discussion This study will provide rigorous clinical evidence evaluating the efficacy and safety of using A&AA as a smoking cessation therapy. Trial registration Chinese Clinical Trial Registry (Registration number: ChiCTR1900028371).